Environmental surveying and surveillance - Awange, Joseph (2018)
© Springer International Publishing AG 2018. In this section, we discuss the quantitative and qualitative data that could be collected using GNSS satellites, and in so doing, attempt to answer the question “what can GNSS satellites deliver that are of use to environmental monitoring?” The observed parameters necessary for environmental monitoring vary, depending upon the indicators being assessed. Some are physical variables such as changes in soil patterns, vegetation, rainfall, water levels, temperature, deforestation, solar and UV radiation. Others are chemical variables, e.g., pH, salinity, nutrients, metals, pesticides, while others are biological variables, e.g., species types, ecosystem health, and indicator species.